Nemesis : Alcibiades and the Fall of Athens - Stuttard, David (Harvard University Press, 2018)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Maps -- Family Tree -- Introduction. Pinning Down Proteus -- Prologue. A Family Divided -- 1. Rearing the Lion Cub -- 2. Coming of Age -- 3. Unbowed in Battle -- 4. Stirring the Hornets' Nest -- 5. Courting the Hydra -- 6. Between Scylla and Charybdis -- 7. Sleeping with the Enemy -- 8. In a Paradise Garden -- 9. Trading Places -- 10. Ruling the Waves -- 11. Dog Days -- 12. Nemesis -- Epilogue. The Shadow of the Dead -- Notes -- Timeline -- Acknowledgements -- Index.